Education of youth and adults: a look at the history of national proposals and the curriculum - Bär, Maira Vanessa; Strieder, Dulce Maria (Revista Hipótese, 2020)
The youth and Adults Education (YAE), established as a modality of basic education under 9.394/96 act, aims at providing the conclusion of Elementary and Middle Schools for youth and adults who, for several reasons, did not finish it at the right term. Thus, in order to perceive YAE reality, this study suggests a bibliographic and documentary review concerning the historical elements of such methodology up from the twentieth century as well as the guidelines that guide it, considering the Curricular Proposal and its guiding axes. Therefore, an overview is structured regarding YAE current conditions.
Keywords: Youth and Adult Education; Basic education; Curricular Guidelines